The Relationship among Overconfidence, Economic Expectation, Social Factors and Investment Decision Making Behavior with the Mediating and Moderating Effects - AHMAD, RIAZ; RIAZ, SAMINA; AQDAS, RAMAISA; HASSAN, SYED IBN UL (The journal of contemporary issues in business and government, 2021)
The current study investigates the relationship among the overconfidence (OVC), economic expectations (EE), social factors (SOF) and investment decision making behavior (IDMB) with the mediating and moderating effect. The data was collected from the investors of Pakistan Stock Exchange (PSX) that were selected through convenience sampling technique. The results of Structural Equation Modeling (SEM) showed that OVC, EE, SOF have a positive and significant relationship with IDMB. On the other hand, OVC, EE, SOF also has a positive and significant relationship with the information search (IS) while IS did not have direct effect on the IDMC. In other words, the IS also did not have mediating effect among the relationship of OVC, EE, SOF and IDMB. The indirect effect further indicated that financial literacy (FL) has a significant moderating effect among the relationship of OVC, EE, SOF and IDMC. Therefore, this moderating effect could be considered a contributions of the study. The research limitations and future directions had also discussed at the end of the study.